Treatments for macular oedema following central retinal vein occlusion: systematic review. Issue 2 (10th February 2014) - Ford, John A; Clar, Christine; Lois, Noemi; Barton, Samantha; Thomas, Sian; Court, Rachel; Shyangdan, Deepson; Waugh, Norman
Abstract : Objectives: To review systematically the randomised controlled trial (RCT) evidence for treatment of macular oedema due to central retinal vein occlusion (CRVO). Data sources: MEDLINE, EMBASE, CDSR, DARE, HTA, NHSEED, CENTRAL and meeting abstracts (January 2005 to March 2013). Study eligibility criteria, participants and interventions: RCTs with at least 12 months of follow-up assessing pharmacological treatments for CRVO were included with no language restrictions. Study appraisal and synthesis methods: 2 authors screened titles and abstracts and conducted data extracted and Cochrane risk of bias assessment. Meta-analysis was not possible due to lack of comparable studies. Results: 8 studies (35 articles, 1714 eyes) were included, assessing aflibercept (n=2), triamcinolone (n=2), bevacizumab (n=1), pegaptanib (n=1), dexamethasone (n=1) and ranibizumab (n=1). In general, bevacizumab, ranibizumab, aflibercept and triamcinolone resulted in clinically significant increases in the proportion of participants with an improvement in visual acuity of ≥15 letters, with 40–60% gaining ≥15 letters on active drugs, compared to 12–28% with sham. Results for pegaptanib and dexamethasone were mixed. Steroids were associated with cataract formation and increased intraocular pressure. No overall increase in adverse events was found with bevacizumab, ranibizumab, aflibercept or pegaptanib compared with control. Quality of life was poorly reported. All studies had a low or unclear risk of bias. Limitations: All studies evaluated a relatively short primary follow-up (1 year or less). Most had an unmasked extension phase. There was no head-to-head evidence. The majority of participants included had non-ischaemic CRVO. Conclusions and implications of key findings: Bevacizumab, ranibizumab, aflibercept and triamcinolone appear to be effective in treating macular oedema secondary to CRVO. Long-term data on effectiveness and safety are needed. Head-to-head trials and research to identify 'responders' is needed to help clinicians make the right choices for their patients. Research aimed to improve sight in people with ischaemic CRVO is required.